When crack was king : a people's history of a misunderstood era - Ramsey, Donovan X. (One World, 2023)
"The crack epidemic of the 1980s and 1990s is arguably the least examined crisis in American history. Beginning with the myths inspired by Reagan's war on drugs, journalist Donovan X. Ramsey's exacting work exposes the undeniable links between the last triumphs of the Civil Rights Movement and the consequences we live with today-a racist criminal justice system, continued mass incarceration and gentrification, and increased police brutality. When Crack Was King follows four individuals to give us a startling portrait of crack's destruction and devastating legacy. Elgin Swift, an archetype of American industry and ambition and son of a crack-addicted father who turned their home into a "crack house"; Lennie Woodley, a former crack addict and a sex worker; Kurt Schmoke, former mayor of Baltimore and an early advocate of decriminalization; and lastly, Shawn McCray, community activist, basketball prodigy, and a founding member of the Zoo Crew, Newark's most legendary group of drug traffickers"--